Contribution Leg Muscle Strength, Dynamic Balance and Hip Joint Flexibility to the Accuracy of Football Shooting - Aminudin Aminudin; Sugiyanto Sugiyanto; Hanik Liskustyawati (BIRCU, 2020)
The purpose of this study was to determine the meaning of the contribution of each independent variable (leg muscle strength, dynamic balance and hip joint flexibility) to the accuracy of football shooting and to find out how meaningful the contribution of the independent variables together to the accuracy of football shooting. This study uses a quantitative descriptive correlational approach with regression analysis design. The sample was extracurricular high school football students in Sidareja with a total of 65 from a total population of 65. Data analysis techniques used regression analysis with the help of SPSS 20. The results of the analysis showed that: (1) X1 made a significant contribution to Y. (2) X2 made a contribution which is significant to Y. (3) X3 gives a significant contribution to Y. (4) X4 gives a significant contribution to Y. In this study it can be concluded that the leg muscle strength variable contributed 22.96%, the variable of diamonic balance is 24 , 28%, the hip joint flexibility variable was 41.26%, while all the independent variables contributed 96.5% to the accuracy of football shooting.